STORAGE OF RAW MATERIALS AND FINISHED MATERIALS OF BAKERY PRODUCTS AT ROTTE BAKERY PEKANBARU - Adella Puspita Sari; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Rotte Bakery Pekanbaru is one of the well-known cake shops in Pekanbaru City. This study aims to find out how the storage of raw materials and finished ingredients for bakery products is carried out by Rotte Bakery Pekanbaru. This study used descriptive qualitative method. Data collection techniques are observation, interviews and documentation. Based on the results of research conducted at Rotte Bakery Pekanbaru, the storage of raw materials and finished materials is good enough so that the products sold are of good quality. The subjects of this research are the Head of Production from Rotte Bakery Pekanbaru and also the employees who work for the company. Keywords: Storage, raw materials, finished materials, products, bakery